2011
DOI: 10.1098/rsbl.2010.1186
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage to DNA related to survivorship and carotenoid-based sexual ornamentation in the common yellowthroat

Abstract: Carotenoid-based sexual ornaments are hypothesized to be reliable signals of male quality, based on an allocation trade-off between the use of carotenoids as pigments and their use in antioxidant defence against reactive oxygen species. Carotenoids appear to be poor antioxidants in vivo, however, and it is not clear whether variation in ornament expression is correlated with measures of oxidative stress (OXS) under natural conditions. We used single-cell gel electrophoresis to assay oxidative damage to erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 19 publications
3
57
0
Order By: Relevance
“…These three measurements were taken for all blood samples, by making three slides per sample (untreated, challenge and repair). In SCGE, DNA damage levels are quantified as the average per cent DNA found in the electrophoresis-generated tail (damaged DNA migrates into tails [10]). In vivo DNA damage levels were quantified on 50 cells of an untreated slide.…”
Section: (C) Oxidative Stress Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…These three measurements were taken for all blood samples, by making three slides per sample (untreated, challenge and repair). In SCGE, DNA damage levels are quantified as the average per cent DNA found in the electrophoresis-generated tail (damaged DNA migrates into tails [10]). In vivo DNA damage levels were quantified on 50 cells of an untreated slide.…”
Section: (C) Oxidative Stress Measuresmentioning
confidence: 99%
“…All analyses were run in duplicate and the intra-and inter-assay coefficients of variation were 4.01 and 4.33% for ROMs, and 3.85 and 4.45% for TAC. We used the SCGE assay [10] with modifications (see the electronic supplementary materials) to measure three distinct aspects of DNA damage and repair: in vivo DNA damage levels, vulnerability of DNA to a H 2 O 2 challenge and DNA repair efficiency. These three measurements were taken for all blood samples, by making three slides per sample (untreated, challenge and repair).…”
Section: (C) Oxidative Stress Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The Journal of Experimental Biology (2014) doi:10.1242/jeb.092825 components in birds (Freeman-Gallant et al, 2011;Noguera et al, 2012). This suggests that increasing antioxidant intake in cold conditions may have adaptive advantages, which may explain why this behavior has evolved.…”
Section: Research Articlementioning
confidence: 96%
“…Antioxidant capacity is positively, while oxidative damage negatively related to survival (Freeman-Gallant et al 2011;Saino et al 2011). Furthermore recent studies showed that the ability of nestlings to cope with oxidative stress predicts their fledging success (Losdat et al 2013) and their recruitment probability (Noguera et al 2012), highlighting that an efficient antioxidant protection is beneficial from the first stages of life.…”
Section: Introductionmentioning
confidence: 99%